HYDROPS FETALIS SECONDARY TO TOXOPLASMA GONDII AND TREPONEMA PALLIDUM COINFECTION: CASE REPORT AND BRIEF LITERATURE REVIEW: case report and brief literature review - Lambert , Mulakwa Morisho; Guillain, Munguakonkwa Mwenge; Ayishabage, Bravo Christian; Serge, Cirimwami Muganda; Ngalo , Maroyi Rodrigue; Serge, Gakne Manikase; Amisi, Bamavu Charles; Byamungu, Ahadi Justin; Kafayo, Kirembe Armand (Student's Journal of Health Research Africa, 2024)
Background Hydrops fetalis is a pathological condition in which fluid accumulates in the fetus in an extracellular environment, leading to subcutaneous edema and possible accumulation in the fetal body and abdominal cavity. The most common causes in this region are infectious, making systematic monitoring during pregnancy essential. However, it is difficult to apply this guideline in urban areas, and even more so in rural areas with few resources for investigation, as in this patient's case, monitoring was ineffective. The aim was to carry out infection studies in maternal blood samples taken after giving birth to a newborn in hydrops. Case presentation A 36-year-old rural woman in her 6th pregnancy presented with uterine contractions in what was thought to be a full-term pregnancy. The progress of this pregnancy had not been monitored throughout the antenatal period for unknown reasons despite a clinical presentation characterized by breathlessness and generalized edema. The obstetric gynecology clinical examination revealed a mattress-like appearance suggestive of placenta previa, and a cesarean section was indicated with the extraction of a newborn with hydrops fetalis who died despite resuscitation efforts. An infectious disease investigation after delivery revealed the presence of both Treponema pallidum and Toxoplasma gondii in the maternal blood sample. Conclusion This state of hydrops fetalis was secondary to this co-infection, which is very difficult to manage in such conditions, facilitated by the lack of systematic biological monitoring for pathogens that could harm both the fetus and the mother. Recommendation Facilitate prenatal visits to women, especially in rural areas where access to services is limited, through home visits from health workers and community relays. During the monthly antenatal visit, pregnant women should be subjected to compulsory infectious screening to provide suitable conditions for the fetus.